One-year surveillance of SARS-CoV-2 in wastewater from vulnerable urban communities in metropolitan São Paulo, Brazil. (11th February 2022) - Barbosa, Mikaela Renata Funada; Garcia, Suzi Cristina; Bruni, Antonio de Castro; Machado, Flávio Silva; de Oliveira, Roberto Xavier; Dropa, Milena; da Costa, Antonio Charlys; Leal, Elcio; Brandão, Carlos Jesus; da Silva, Renan Lourenço Oliveira; Iko, Beatriz Yukie; Kondo, Victor Kenji Matsuoka; et al.
Abstract: The current COVID-19 pandemic has emphasized the vulnerability of communities living in the urban outskirts and informal settlements. The lack of reliable COVID-19 case data highlights the importance and application of wastewater-based epidemiology. This study aimed to monitor the COVID-19 trends in four vulnerable urban communities (slums and low-income neighborhoods) in metropolitan São Paulo by assessing the SARS-CoV-2 RNA viral load in wastewater. We analyzed 160 samples from May 2020 to June 2021 with weekly or fortnightly samplings. The samples were ultracentrifuged with glycine elution and quantified by N1/N2 SARS-CoV-2 RT-qPCR. The results of positivity were 100% (Paraisópolis, Heliópolis and Cidade Tiradentes) and 76.9% (Vila Brasilândia). The new case numbers of COVID-19, counted from the onset of symptoms, positively correlated with SARS-CoV-2 N1 viral loads from the two largest communities ( p <0.001). SARS-CoV-2 infectivity was tested in Vero E6 cells after concentration with the two techniques, ultrafiltration (Centricon ® Plus-70 10 kDa) and sucrose cushion ultracentrifugation, but none of the evaluated samples presented positive results. Next-generation sequencing (NGS) analysis from samples collected in March and August 2021 revealed the presence of the clade 20 J (lineage P.1) belonging to the most prevalent circulating variant in the country. Our results showed that wastewater surveillance data can be used as complementary indicators to monitor the dynamics and temporal trends of COVID-19. The infectivity test results strengthened the evidence of low risk of infection associated with SARS-CoV-2 in wastewater. HIGHLIGHTS: SARS-CoV-2 WBE can be a valuable tool to follow trends of COVID-19 cases in vulnerable communities (slums and low-income neighborhoods). Positive samples for SARS-CoV-2 RNA presented negative results in the infectivity assays performed with Vero E6 culture cell. Preliminary results of NGS sequencing analysis showed the circulation of lineage P.1, the predominant SARS-CoV-2 variant in clinical genomic surveillance Graphical Abstract